Redesign Interior Rumah Sakit Hewan Universitas Airlangga Surabaya - Agnes Tania (Intra, 2017)
Animals that treated and loved may suffer from disease and require special care. One of the best solutions is visiting the Animal Hospital. It is a center for animal health with complete rooms and facilities in accordance with the provisions. Animal Hospital of the Faculty of Veterinary Medicine of Airlangga University (UNAIR) is one of the hospital that serve the community in the field of animal health. Unfortunately, the existence of this animal hospital is rarely known by the people of Surabaya. Several rooms at UNAIR Animal Hospital due to its low appearances and performances such as bleak look, low standard, damage on several interior elements and inappropriate function in rooms design. By rearranging the location and function of the room and redesign the colors and shapes in accordance with the brand image of the hospital blue and yellow on interior elements and furnishings that symbolize trust and warmth in accordance with the vision of the hospital and the application of professional and modern concepts. Redesign and rebranding are expected to improve the quality of animal hospital , staff efficiency, and public interest. Design method used is through design thinking, including observation, brainstorm, prototype, and implementation.